(untitled) (Research, Society and Development, 2022)
Objective: to map the literature on the applicability of the Tidal Model by nurses in mental health services. Method: Scope review which followed the recommendations of the Joanna Briggs Institute Evidence Manual, using the strategy for preparing the research question of the Person, Concept, Context (PCC) type, had as a research question: how is the applicability of the Tidal Model by nurses in mental health services? The search terms ’nursing’, ’mental health’ and ’Tidal Model’ were used. Adopted research flow proposed by PRISMA-ScR. Collected in August 2021, 12 articles were selected from the journals indexed in the PUBMED, CINAHL, Web of Science, SCOPUS and LILACS databases. Results: the information extracted from the studies allowed the construction of the categories: application context; service user profile; actions for institutional implementation; challenges for applicability; nursing care; Nurse-People relationship and care outcomes. Conclusion: The Tidal Model is applied according to the nature of the need that the person presents, obeying the three dimensions that comprise it. It is a versatile theory that fits the context of the service. At the institutional level, its implementation must follow processes for the incorporation of the fundamentals that guide the practice. Studies regarding the applicability of this theory in the context of Brazilian mental health services are still scarce.